INTERFERENSI FONOLOGIS BAHASA JAWA TERHADAP FONEM BAHASA INDONESIA: KAJIAN SOSIOLINGUISTIK (Javanese Phonological Interference with Indonesian Phonemes: A Sociolinguistic Study) - Tiarma Rokasih Sagala; Andini Ridwana; Sri Rahma Haryanti; Mirna Putri Aulia; Anggia Putrie (Yayasan Panca Bakti Wiyata Pangandaran, 2025)
This research aims to analyze Javanese phonological interference with Indonesian, including its form, causal factors, and implications in the social context of education. The interference of the phoneme /f/ becomes /p/ or /v/ becomes /b/. Factors such as bilingualism, the need for synonyms, and lack of mastery of a second language are the main causes of this phoneme. This research uses a qualitative method based on library research, with critical analysis of relevant literature sources. The research results show that phonological interference has an impact on pronunciation in everyday communication and language learning, often mixing elements from two languages. To overcome this problem, an integrative approach in education is recommended, such as educational policies encouraging the use of regional and national languages in a balanced manner. These findings provide in-depth understanding, as well as strategic steps to maintain cultural identity without reducing competence in Indonesian.